Criteria for Early Pacemaker Implantation in Patients With Postoperative Heart Block After Congenital Heart Surgery. (28th October 2022) - Duong, Son Q.; Shi, Yuan; Giacone, Heather; Navarre, Brittany M.; Gal, Dana B.; Han, Brian; Sganga, Danielle; Ma, Michael; Reddy, Charitha D.; Shin, Andrew Y.; Kwiatkowski, David M.; Dubin, Anne M.; et al.
Abstract : Background: Guidelines recommend observation for atrioventricular node recovery until postoperative days (POD) 7 to 10 before permanent pacemaker placement (PPM) in patients with heart block after congenital cardiac surgery. To aid in surgical decision-making for early PPM, we established criteria to identify patients at high risk of requiring PPM. Methods: We reviewed all cases of second degree and complete heart block (CHB) on POD 0 from August 2009 through December 2018. A decision tree model was trained to predict the need for PPM amongst patients with persistent CHB and prospectively validated from January 2019 through March 2021. Separate models were developed for all patients on POD 0 and those without recovery by POD 4. Results: Of the 139 patients with postoperative heart block, 68 required PPM. PPM was associated with older age (3.2 versus 1.0 years; P =0.018) and persistent CHB on POD 0 (versus intermittent CHB or second degree heart block; 87% versus 58%; P =0.001). Median days [IQR] to atrioventricular node recovery was 2 [0–5] and PPM was 9 [6–11]. Of the 100 cases of persistent CHB (21 in the validation cohort), 59 (59%) required PPM. A decision tree model identified 4 risk factors for PPM in patients with persistent CHB: (1) aortic valve replacement, subaortic stenosis repair, or Konno procedure; (2) ventricular L-looping; (3) atrioventricular valve replacement; (4) and absence of preoperative antiarrhythmic agent (in POD 0 model only). The POD 4 model specificity was 0.89 [0.67–0.99] and positive predictive value was 0.94 [95% CI 0.81–0.98], which was stable in prospective validation (positive predictive value 1.0). Conclusions: A data-driven analysis led to actionable criteria to identify patients requiring PPM. Patients with left ventricular outflow tract surgery, atrioventricular valve replacement, or ventricular L-Looping could be considered for PPM on POD 4 to reduce risks of temporary pacing and improve care efficiency.